Cluster analysis of socio-economic factors and academic performance of school students - Kapila Devi; Saroj Ratnoo (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The objective of the paper is to examine the academic performance of students’ vis-a-vis socio-economic factors using clustering analysis. The grades obtained in the 10th class are taken as the measure of academic performance. The variables such gender, caste, parental education and occupation. are considered as the socio-economic indicators. Three clustering algorithems are employed. The K-medoid performs better in the validation process to form the groupings based on intra-cluster homogeneity and inter-cluster heterogeneity. The clustering analysis results in two interesting groups of the students. One of the clusters is dominated by the students of general category and the other one by the scheduled caste category. Next, the appropriate statistical tests are applied to determine the factors that significantly differ in the two clusters. Cluster analysis shows that caste, parents' education and occupation, and family income are the differentiating factors between the two groups. However, we are unable to establish significant difference between the academic performance of the two groups of students at a 5% significance. The research carried out in this paper may be beneficial for making policies to bridge the gap in the educational attainment of the students from deprived sections of society.